2015
DOI: 10.1089/end.2014.0636
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral Holmium Laser Cystolithotripsy in Children: Single Center Experience

Abstract: Ho:YAG laser CL is a safe and successful minimally invasive treatment option for bladder stones in children. Success rate was 100% without development of any complications or recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
(29 reference statements)
2
11
0
1
Order By: Relevance
“…Voiding dysfunctions, foreign bodies, urethral strictures, PUV and vesicoureteral reflux predispose children to vesicolithiasis. 11 Lal et al reported that the incidence of vesical stone in children is slowly declining. This is predominantly due to nutritional improvement, better pre-and postnatal care and improvement of the people's awareness in the endemic areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Voiding dysfunctions, foreign bodies, urethral strictures, PUV and vesicoureteral reflux predispose children to vesicolithiasis. 11 Lal et al reported that the incidence of vesical stone in children is slowly declining. This is predominantly due to nutritional improvement, better pre-and postnatal care and improvement of the people's awareness in the endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…13 Development in pediatric ureteroscopes and cystoscopes and presentation of Ho:YAG laser, causes a steady shift to TULL in children's bladder stone management. 11 Several studies have mentioned the advantages of Ho:YAG laser lithotripsy for managing vesical lithiasis, in comparison with other choices. 10 Traditionally, open surgery was the choice of treatment for large bladder stone (>4 cm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ho:YAG laser lithotripsy is an efficient and safe technology for the treatment of urinary stones in almost any patient group, ranging from young children to adults and older patients, pregnant women to spinal cord injury patients, from solitary to allograft kidneys, or patients on certain medications and anticoagulants. Its safety profile has been largely demonstrated and still is in countless and recent safety-oriented studies [ 87 •, 88 •, 89 , 90 •, 91 98 , 99 •, 100 , 101 •]. Yet there are still some direct and indirect complications and safety concerns about laser lithotripsy, which have been recently researched.…”
Section: Bibliographic Search Resultsmentioning
confidence: 99%
“…Çocuklarda transüretral holmium lazer litotripsi yapılan ve < 4 cm mesane taşı olan 33 çocuk hastanın dahil edildiği bir çalışmada çocukların tamamında ortalama 31 dakika sürede taşsızlık sağlanmış ve hiçbir hastada üreteral darlık veya rekürren taş gözlenmemiştir (16). Çocuklarda mesane taşlarında pnömotik litotripsi ve holmium lazer litotripsinin karşılaştırıldığı bir çalışmada 13 hastaya pnömotik, 12 hastaya ise holmium lazer litotripsi uygulanmıştır.…”
Section: Pediatrik Taş Hastalarında Lazer Litotripsiunclassified